Image Processing Based Approach for Crime Scene Investigation Using Drone - Gur, Alper; Erim, Mehmet; Karakose, Mehmet (Institute of Electrical and Electronics Engineers Inc., 2020)
Time management at the crime scene is very difficult. It is necessary to make good use of time and examine the evidence at the scene without any damage and deterioration from life. There may be evidences that are overlooked in a short time and places where experts cannot reach the evidence or situations that may endanger the safety of experts. In this study, the crime scene investigation system with an autonomous drone was investigated. With the help of the drone, data was collected to help examine the evidence. Thus, in examining the evidence; time savings, securing the crime scene investigator and more data will be obtained. Remote control and autonomous driving feature has been written for the drone. The camera placed on the drone, the images of the evidence at the scene were taken thanks to the cameras. The inferences obtained from the images are transferred to the user with the artificial intelligence supported model created. In order to process these data, it was given as an introduction to the model created after preparation and the training of the model was provided. As a result of the training of the model, the images taken on the drone can be detected through the software developed with the support of real-time artificial intelligence. These detected objects are transferred to the scene investigation specialist on the interface screen in real time, thereby developing a system with both artificial intelligence control and user supervision. © 2020 IEEE.
2020 International Conference on Data Analytics for Business and Industry: Way Towards a Sustainable Economy, ICDABI 2020 -- 26 October 2020 through 27 October 2020 -- Sakheer -- 166670
Keywords: autonomous drone; crime scene investigation; object detection